Disulfiram alleviates acute lung injury and related intestinal mucosal barrier impairment by targeting GSDMD-dependent pyroptosis - Jiping Zhao; Hong Wang; Jintao zhang; Fuwei Ou; Junfei Wang; Tian Liu; Jinxiang Wu (Journal of Inflammation, 2022)
Abstract Background Pyroptosis was implicated in acute lung injury (ALI). Disulfiram is reported as an effective pyroptosis inhibitor by inhibiting gasdermin D(GSDMD). However, the function of pyroptosis executor GSDMD and treatment of disulfiramon on ALI, especially whether it was involved in ALI-associated intestinal mucosal barrier impairment remains unclear. This study aims to explore the role of pyroptosis and disulfiram’ treatment on ALI and related intestinal mucosal barrier impairment. Methods First, we established lipopolysaccharide (LPS)-induced ALI models in wild-type and Gsdmd knockout (Gsdmd −/−), to detect the effect of pyroptosis on ALI-related intestinal mucosal barrier impairment. Furthermore, we used wild-type mice treated with disulfiram to investigate the treatment of disulfiram on ALI and related intestinal mucosal barrier impairment. Results The data showed that GSDMD-mediated pyroptosis was activated in both lung and intestinal mucosa tissues in LPS-induced ALI, and deficiency of Gsdmd ameliorated LPS-induced ALI and related intestinal mucosal barrier damage. We also disclosed that disulfiram inhibited the pyroptosis level, and alleviated ALI and related intestinal mucosal barrier impairment induced by LPS. Conclusion These findings suggested the role of GSDMD-mediated pyroptosis and the potential application treatment of disulfiram in ALI and related intestinal mucosal barrier damage.